2023
DOI: 10.3390/cryst13050789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Nanotubes on the Mechanical, Thermal, and Electrical Properties of Tin-Based Lead-Free Solders: A Review

Liangwei Li,
Weiou Qin,
Baohua Mai
et al.

Abstract: Carbon nanotubes (CNTs) are being applied with increasing frequency for advanced soldering. They have excellent mechanical, electrical, and thermal properties and are primarily used to reinforce lead-free solders. This paper discusses the strengthening mechanism of CNTs, introduces the preparation methods of CNT composite solders, and focuses on the review of tin-based lead-free solders reinforced with unmodified CNTs and metal-modified CNTs. The addition of CNTs can effectively improve the ultimate tensile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…However, potential interference, limited communication range, power consumption, and higher initial costs remain as limitations. Carbon nanotubes (CNTs) are a promising nanomaterial for strain sensors because of their outstanding mechanical and electrical properties; also, it possesses a high aspect ratio and very low density [ 3 , 4 , 5 , 6 ]. Enormous studies showed the feasibility of using CNTs-based thin films for strain sensing, their unique physical mechanism for measuring strain is based on how electrical resistance changes in response to applied mechanical stress, allowing for accurate and reliable measurements [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, potential interference, limited communication range, power consumption, and higher initial costs remain as limitations. Carbon nanotubes (CNTs) are a promising nanomaterial for strain sensors because of their outstanding mechanical and electrical properties; also, it possesses a high aspect ratio and very low density [ 3 , 4 , 5 , 6 ]. Enormous studies showed the feasibility of using CNTs-based thin films for strain sensing, their unique physical mechanism for measuring strain is based on how electrical resistance changes in response to applied mechanical stress, allowing for accurate and reliable measurements [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%